The attainment of our desires - Conwell, Rachel Callie (My University, 1891)
Introduction: Every human life has its purpose and everything in nature its uses, and, however much we may desire to evade the responsibilities which rest in each individual, or absorb them in the general application to the race, or to whatever, extent we may throw ourselves on the soothing straight—“There is a Divinity that shapes our ends. Rough hew them how we will;” still ever within us there is a consciousness which tells us that in the duties of life, everyone must answer for himself and not for another. This very consciousness is the key note of existence, lending to life its charms and to society its surest safeguards. The possession of a clear pure conscience is held dear by each and every one of us. We are constantly striving to follow such occupations and pursuits as will best afford us this quality.
Citation: Conwell, Rachel Callie. The attainment of our desires. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Human life; Purpose; Desire; Responsibility; Theses; Manuscripts (documents)